Trends in Anti-VEGF Injection Medicare Part B Claims among Male and Female Ophthalmologists from 2012-2016. (17th November 2021) - Pradeep, Tejus; Melachuri, Samyuktha; Arun, Siddharth; Ravipati, Advaitaa; Wang, Serena; Zhang, Matthew; Errera, Marie Helene; Fu, Roxana
ABSTRACT: Background : Compared to male ophthalmologists, female ophthalmologists have significantly reduced salaries, fewer faculty roles and authored publications, garnered less federal research funding, and achieved less editorial advancement. We aimed to use the most recently available Centers for Medicare and Medicaid Services data to characterize trends and differences in anti-VEGF reimbursements coded for by male and female ophthalmologists. Methods : We used Medicare Fee-For Service Provider Utilization and Payment Data: Part B Provider public use files for 2012–2016 to quantify service and reimbursement patterns for anti-VEGF injections between male and female ophthalmologists. Five outcome variables were studied: number of providers, average Medicare payment amount, total payment, number of services, and number of Medicare beneficiaries. Results : Number of services performed per female provider was 71.2% that of a male ophthalmologist in 2012, and this percentage did not change from 2012 to 2016 (95%CI [0.63, 0.804], [0.984, 1.04], respectively). Female providers had 76.1% of beneficiaries as males in 2012, and this percentage stayed constant throughout the years (95%CI [0.69, 0.84] and [0.99, 1.03], respectively). The total payment difference between female and males was $102, 175 per provider in 2012, and this gap widened by $18, 292 yearly (95% CI [−162599.17, −41760.47], [−33060.35, −3524.38], respectively). Conclusion : While male and female providers saw considerable increases in aflibercept services and payments in the 5-year period, the gap between male and female reimbursements widened significantly. Moving forward, analysis of large-scale Medicare datasets provides a tangible report card on how effective our attitudes and policies are in cultivating equal opportunity.